The Effect of Health Education Based on the Health Belief Model about Pap Smear Test on Women in Rural District Indonesia (Medico Legal Update, 2021)
Background: The aim of this study was to evaluate the effectiveness of educational interventions based onHealth Belief Models (HBM) on the adoption of cervical cancer screening and prevention behaviours inIndonesian women in a rural district.Method: This is a quasi-experimental study with pre-test and post-test design. The convenience samplingwas used and a total of 100 women participated in this study. One hour educational intervention based ona health belief model including lectures, question and answer, group discussions and booklets on cervicalcancer and cervical cancer screening provided to participants. The content of the session included basicinformation regarding cervical cancer facts, important early detection, recommended screening method,guidelines for Pap smear screening and the role of pap smears in early diagnosis of cervical cancer. Aswell as, pamphlets distributed to participants. Post-test test hold within six months after the end of theintervention.Results: The findings showed that the mean difference of the scores before and after health educationalintervention about Pap smear and cervical cancer for all constructs (except; perceived susceptibility andseverity were no changes) has increased significantly with P-value